Aspulvinones Suppress Postprandial Hyperglycemia as Potent α-Glucosidase Inhibitors From Aspergillus terreus ASM-1 - Wu, Changjing; Cui, Xiang; Sun, Luzhen; Lu, Jiajia; Li, Feng; Song, Minghui; Zhang, Yunxia; Hao, Xinqi; Tian, Congkui; Song, Maoping; Liu, Xiaomeng (Frontiers in Chemistry, 2021)
Chemical investigation of Aspergillus terreus ASM-1 fermentation resulted in the isolation of three new prenylated aspulvinones V–X (1–3), together with the previously reported analogs, aspulvinone H (4), J-CR (5), and R (6). Their structures were elucidated by various spectroscopic methods including HRESIMS and NMR, and the absolute configurations of 2 and 3 were determined by ECD comparison. Compounds 1–6 were evaluated for α-glucosidase inhibitory effects with acarbose as positive control. As a result, compounds 1 and 4 exhibited potent α-glucosidase inhibitory activities with IC50 values of 2.2 and 4.6 µM in mixed-type manners. The thermodynamic constants recognized the interaction between inhibitors and α-glucosidase was hydrophobic force-driven spontaneous exothermic reaction. The CD spectra also indicate that the compounds 1 and 4 changed the enzyme conformation. Furthermore, compound 4 significantly suppressed the increases in postprandial blood glucose levels in the C57BL/6J mice.